Analisis Dinamika Kelompok Tani Tembakau (Studi Kasus di Kelompok Subur Tani 1, Desa Sukasari, Kecamatan Sukasari, Kabupaten Sumedang) - Maulana, Rifdi Nur; Setiawan, Iwan (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Group dynamics are an essential factor in determining the effectiveness and sustainability of farmer group activities. This study was conducted on the Subur Tani 1 Group in Sukasari Village, Sukasari District, Sumedang Regency. Respondents were purposively selected, consisting of all 23 group members. The research employed a qualitative approach with a case study strategy, combined with Likert scale analysis of nine elements of group dynamics: group objectives, group structure, task functions, group development and maintenance, cohesiveness, group atmosphere, group pressure, group effectiveness, and hidden agendas. The findings show that Subur Tani 1 is categorized as dynamic, with a score of 2,741 equal to 96.82%. Group atmosphere and group pressure achieved perfect scores, reflecting strong internal conditions. The main strengths include cohesiveness, effective leadership, organizational structure, and open communication. Despite challenges such as limited land, fertilizer, and labor, the group successfully cultivated tobacco three times a year. These results emphasize that strong group dynamics strengthen solidarity and ensure the sustainability of farming activities.